Globalized, Resilient, Dynamic : The New Face of Latin America and the Caribbean - World Bank (Washington, DC, 2017)
Many countries in the Latin America and the Caribbean (LAC) region, especially in South America, fared well during the global crisis and are now on a strong growth path. The region s recession in 2009 was relatively short lived and, with the notable exception of Mexico, remarkably mild. The current pace of economic recovery is exceeding expectations, with gross domestic product (GDP) projected to grow in the 5-6 percent range in 2010. This report discusses LAC's newfound resilience in the midst of financial globalization, examining key features of the cyclical behavior of LAC economies in comparison to other emerging economies and to its own past. Resilience is defined throughout this report in a broad sense to denote the ability of an economy to navigate with minimum disturbances through shocks, cushioning their negative spillovers in bad times, and recovering fast after a downturn. The report is structured as follows: first, it evaluates the relative performance of LAC countries during the contractionary period generated by the recent global crisis, to shed light on LAC's ability to shield its economies or soften the blow of a large external shock. Second, a similar exercise is conducted for the recovery phase of the cycle, when in the aftermath of an external shock more resilient countries will be expected to have a faster and more robust recovery. Third, it takes a deeper look at the different driving forces behind the recovery, including the role of domestic demand, commodity prices, and the connection to emerging Asia. Fourth, it provides evidence of the ability of different countries in LAC to conduct counter-cyclical policies in response to the global financial crisis. Lastly, a concluding section warns about the main macro-financial tensions and challenges lying ahead for the region.